Analysis of the daylight performance of a glazing system with Parallel Slat Transparent Insulation Material (PS-TIM) - Sun, Yanyi; Wu, Yupeng; Wilson, Robin (Elsevier, 2017)
Daylight plays an important role in the energy efficiency and indoor environmental quality of an office building. An innovative façade system where parallel transparent/translucent plastic slats are sandwiched between glass panes to form a Parallel Slat Transparent Insulation Material (PS-TIM) is proposed as a strategy to effectively increase the thermal resistance of window systems, while providing better daylight performance. In this paper, the optical performance (as defined by Bidirectional Scattering Distribution Function) of a double glazed window containing PS-TIM systems with different slat pitches (the distance between neighbouring slats), slat tilt angles, as well as the slat materials (transparent and translucent) was obtained using a ray-tracing technique. Then, the annual daylight performance of a typical office building with various PS-TIM applied under different climatic conditions and at different orientations was investigated using RADIANCE. The simulation results show that PS-TIM with translucent slats offers better daylight performance than conventional double glazing: it can increase the percentage of annual working hours under daylight, where the illuminance lies in the useful range by up to 79%. It also achieves a homogenous distribution of daylight within the internal working space and effectively reduces the possibility of glare. When applying PS- TIM at higher site latitude, smaller slat pitches are required to maximise useful daylight. Optimised PS-TIM geometry is also affected by local prevailing sky conditions.